Unveiling the Dichotomy: Exploring Iqbal’s Concept of Khudi and Bekhudi - Dr. Ambreen Ashraf; Prof. Dr Ismat Ullah Cheema; Mr. Muhammad Adnan; Mr. Muhammad Furqan Ayyub (Dialogue Social Science Review (DSSR), 2025)
This article examines the complex philosophical dichotomy between Khudi (selfhood) and Bekhudi (self-effacement) in the poetic and intellectual legacy of Dr. Muhammad Iqbal, a known poet in the literacy history of the Indian subcontinent. While Khudi is frequently understood as a call toward self-affirmation, spiritual empowerment, and the actualization of one's inner potential, Bekhudi appears to advocate a surrender of the self—seemingly contradicting Iqbal’s otherwise assertive vision of human agency. This paper investigates how Iqbal harmonizes these two notions within a coherent metaphysical and ethical framework, drawing on the rich traditions of Persian Sufism, classical Islamic philosophy, and Nietzschean ideas of self-realization. Through a close reading of Iqbal’s major philosophical poems—Asrar-e-Khudi and Rumuz-e-Bekhudi—the study reveals how these intertwined concepts inform not only personal spiritual growth but also the collective consciousness and moral evolution of the Muslim Ummah.